Uji Kelarutan Ramipril dengan Koformer Nicotinamide - M. Ramadhan Saputro; Muhamad Reza Pahlevi; Diki Zaelani; Dean Al-Ayubbi; Siti Hanif (STIKes Ibnu Sina Ajibarang, 2025)
Ramipril (RMP) is one of the drugs that has antihypertensive activity. The drawback of the active substance Ramipril is that it is difficult to dissolve, and is classified in Class II in the Biopharmaceutical Classification System. So it needs to be modified with a cocrystal technique to increase solubility without having to change the activity of the active substance. The coformer used to make the cocrystal is nicotinamide. The purpose of this study was to increase the solubility of Ramipril with Nicotinamide coformer. The method in making this cocrystal is Solvent Drop Grinding (SDG) with a ratio of Ramipril: Nicotinamide (1: 2 and 1: 4) using methanol solvent. Then the cocrystal and pure Ramipril will be subjected to characterization tests with FTIR and solubility tests with UV spectrophotometry at a wavelength of 206 nm. The results of the characterization with FTIR prove that a hydrogen bond is formed between Ramipril-Nicotinamide. Then for solubility in aquadest, RN cocrystal 1:2 and 1:4 have higher solubility which is 5.11 mg/mL and 6.71 mg/mL compared to pure Ramipril which has a solubility of 1.69 mg/mL. The conclusion of this study is that RN cocrystal (1:2 and 1:4) has higher solubility compared to pure Ramipril.